Educational Equality For Children With Special Needs In The World Of Education - Yenti, Reffika Suci Syafitri Reffli; Yeni, Putri; Fitriyani, Wahidah; Idris, Adam (Yayasan Minang Darussalam, 2024)
Inclusive education is an educational model for realizing education for all children, including for CWD. Inclusive education provides equal opportunities to CWD and creates education which respects for diversity, and not discriminatory. Inclusive is also intended to promote social change and social values by construct community awareness of reducing discriminatory values and attitudes. CWD often gets discriminatory treatment and difficulties in accessing education so it needs to implement an inclusive education model as a solution. The method used in writing this article is the literature review method. In this article it was found that the inclusive education model needs to be implemented in the education system as an effort to realize equality and non-discrimination for CWD as revealed by several researchers. The implementation of inclusive education needs to pay attention to the resources and needs that support the realization of inclusiveness. However, in implementation inclusive education still experiences various problems and obstacles. Inclusive education can have positive and negative impacts on CWD. Good social acceptance in the environment can have a positive impact, whereas poor social acceptance can have a negative impact on CWD. Social workers have an important role in implementing inclusive education.